New targeted therapies in the treatment of patients with metastatic melanoma - Mackiewicz, Jacek; Kwinta, Łukasz (Contemporary Oncology/Współczesna Onkologia, 2010)
The incidence of melanoma is increasing rapidly both in Poland and worldwide. In Poland melanoma is a rare malignancy with about 2200 new cases annually. Results of the treatment at the time of inoperable metastases occurrence (stage IV) are unsatisfactory. Completed phase III clinical trials evaluating the efficacy of several cytotoxic agents and biological therapies did not produce the intended result. In daily oncological practice the most commonly used agent in the treatment of metastatic melanoma is still dacarbazin, with the median overall survival equal 6 months. High expectations are connected with targeted therapy – kinase inhibitors, monoclonal antibodies, antisense therapy and PARP inhibitors. Ipilimumab (antibody anti-CTLA4) and oblimersen sodium (oligodeoksynucleotide targeted against Bcl-2 gen) are currently being evaluated in phase III clinical trials. Molecules targeting MEK kinase (AZD6244), mTOR (everolimus, temsirolimus) and VEGFR (axitinib) or monoclonal antibodies directed against VEGF (bevacizumab) or 51 integrin (volociximab) are demonstrating some activity in the early phase trials. Multiple new molecules have demonstrated some efficacy (MDX-1106; BMS-66353; CP 870.893; PLX4032) in phase I trials, which activity will have to be confirmed in the next phase trials. Some receptor tyrosine-kinase inhibitors (imatinib, dasatinib or sunitinib) may play a role in the treatment of melanoma patients with c-KIT mutation. The future of the rational use of new targeted agents will depend on the possibility of selecting groups of patients responding to personalized treatment.